Surface Morphological Alterations of An Indigenously Developed Bioceramic Phosphate-Based Cement: Ceremagnum Plus as An Indirect Pulp Capping Agent: An Invitro Study - Mitra, Anusua; Karobari, Mohmed Isaqali (Journal of Neonatal Surgery, 2025)
The present study investigates the amorphicity and crystallinity of a newly developed phosphate-based bioceramic cement, Ceramagnum Plus, formulated to enhance bioactivity and mechanical properties. The composition includes potassium magnesium phosphate (KMgPO₄), tricalcium silicate (CaSiO₃), cerium oxide (CeO₂), zirconium oxide (ZrO₂), and sodium fluoride (NaF), with controlled particle size to optimize setting behavior. The addition of CaSiO₃ promotes the formation of an amorphous silico-phosphate phase, balancing the crystalline MgKPO₄·6H₂O structure, as described in previous studies (Tay et al., 2007). The powders were finely ground to 400 mesh for improved homogeneity, consistency, and reaction kinetics. The scanning electron microscopy (SEM) analysis revealed a heterogeneous microstructure, characterized by fine granular and needle-like structures, suggesting a well-integrated amorphous and crystalline phase. Comparative SEM analysis with MTA Angelus White, a widely used endodontic material, demonstrated finer particle size (0.5–2 µm) in Ceramagnum Plus, compared to larger granules (1–5 µm) and aggregates (~20 µm) in MTA, which may contribute to enhanced handling properties and controlled ion release. The presence of fluoride and cerium oxide in Ceramagnum Plus is expected to improve antibacterial activity, remineralization potential, and radiopacity. This study highlights the structural advantages of Ceramagnum Plus over conventional MTA, providing a promising alternative for dental and orthopedic applications. Future investigations will focus on hydration kinetics, mechanical properties, and in vitro bioactivity to further validate its clinical potential.